Critical upheaval buckling forces of sandwich pipelines with variable stiffnesses of pipe material. (1st December 2020) - Zhao, Tianfeng; Yu, Fajun
Abstract: The upheaval buckling of sandwich pipelines may cause damage to the core material in the buckle, and the changed pipe material stiffness makes such instability problems more complicated. In this paper, the complementary error function is selected to describe the reduction in the stiffness of the pipe material along the sandwich pipe buckle to propose a new buckling characteristic equation for the sandwich pipeline. Green's function for the differential equation for the deflection curve of the variable stiffness of a beam is utilized to portray the upheaval buckle configuration for a precise critical buckling axial force calculation. Three classical imperfection shape functions to account for possible undulations of the seabed or the furrow bottom are induced to modify the critical buckling axial force considering out-of-straightness effects. Highlights: A new buckling characteristic equation is developed, including the changed bending stiffness along the sandwich pipeline buckle. The Green Function Method is utilized to determine the buckle deflection when the complementary error function is employed to fit the bending stiffness. The critical upheaval buckling forces of sandwich pipelines are explicitly expressed analytically with the description of the effect of initial imperfections under the integral form.